PENGARUH MASA KERJA, JABATAN, DAN JENJANG PENDIDIKAN TERHADAP TINGKAT PEMAHAMAN APARATUR PEMERINTAH TENTANG PRIPSIP–PRINSIP GOOD GOVERNANCE DI PEMERINTAH KOTA BANDA ACEH - Muhammad Arfan; Edi Faisal (Jurnal Telaah dan Riset Akuntansi, 2009)
The objective of this research is to examine and analyze the influence of servicing period, position, and education level toward the level of understanding of government officials about the principles of good government governance in the Government of Banda Aceh City. The research type used in this research is verificative research or hypothesis testing research.Respondents in this study amounted to 82 respondents as the sample of the total population of 459 respondents, namely Banda Aceh City government officials who served as Eselon II and Eselon IV of the government services and boards in the Government of Banda Aceh City. Data used in this study are primary data obtained by conducting field research by distributing questionnaires to the respondents directly. All questionnaires can be returned by respondents.Based on the descriptive analysis of the government officials, score of the level of understanding of government officials about the principles of good government governance is obtained by 79.76%. Based on the acquisition of this score can be said that the level of understanding of government officials about the principles of good government governance in the Government of Banda Aceh City is high. The independent variables in this study are presented in the form of dummy variables. Based on the results of hypothesis testing, it is showed that the servicing period and education level have influence toward the level of understanding of government officials about the principles of good governance in the Government of Banda Aceh City, while the position does not have influence toward the level of understanding of government officials about the principles of good governance in the Government of Banda Aceh City.